KEMITRAAN PEMERINTAH SWASTA (Studi Pengelolaan Sampah Menjadi Tenaga Listrik Dengan Program Zero Waste City di PLTSa Benowo, Kota Surabaya) - Borhanudin Achmad Safi; Mas Roro Lilik Ekowanti (Faculty of Social and Political Science, 2022)
In an effort to reduce the volume of waste and to create a clean city, Surabaya City Government conducted a private-government partnership. The partnership exists between the Green Open Space Cleaning Institution (DKRTH) and PT. Sumber Organik (SO). They use Build Operate Transfer Cooperation Model to change the waste into electricity energy at Benowo, Surabaya City. This partnership aims to overcome the waste problem in Surabaya. This research uses qualitative method with data collection techniques of interviews, observation, and documentation. The results of this study indicate that the government-private partnership between DKRTH and PT. SO in managing waste into electricity at PLTSa Benowo Surabaya City has been done effectively. There are 3 aspects that have been effective, namely monitoring and implementation of partnerships, negotiation processes and equal roles, but the aspects that have not been effective are transparency and commitment. In this case the author provides recommendations to pay more attention to the public to get an information about the management become electricity at PLTSa Benowo. Besides that, it needs to improve the management more transparent to the public and tp increase the public trust to the parnership